Alteraciones en la memoria de pacientes postCOVID-19 que reciben atención en el Centro de Salud Universitario de Motupe, 2021 - Romero Torres, Samanta Valeria (2022)
Memory is one of the most important capacities of the human being, since it allows us to store in our brain all kinds of information, memories, knowledge and experiences that are useful for our daily lives. The alteration of it causes problems that interrupt daily activities. With this precedent, the present investigation determined the alterations in the memory of post-COVID-19 patients who received care at the Motupe University Health Center. This research had a total of 100 participants who received home visits in order to apply some psychological instruments. The methods used were exploratory, descriptive and correlational; observation and data collection techniques were applied and two evaluation instruments were used. The Neuropsi Test and the Memory Failure Questionnaire in Daily Life (MFE-30). The results show that within this population there is no higher rate of people with memory disorders. The correlation between memory failures and the severity levels of COVID-19 was also established, showing an insignificant relationship between these two variables